Cavitation erosion behavior of nitinol coating sealed by epoxy resin. Issue 11 (10th November 2020) - Shi, Z.P.; Wang, Z.B.; Qiao, Y.X.
Abstract: The nitinol coating against cavitation erosion was prepared by air plasma spraying and sealed with epoxy resin successfully. After the coating sealed with epoxy resin, the pores and cracks of the coating were filled with the epoxy resin and then the cohesiveness between the lamellae was improved, the hardness increased from 3.68 GPa to 7.49 GPa, the energy recovery ratio (superelasticity) was improved from 41.9 % to 49.0 % and the toughness was enhanced from 0.011 GPa to 0.045 GPa. During the cavitation erosion test, the epoxy resin reduced the cavitation resources and absorbed the impact energy from the micro‐jet or shock waves. Meanwhile, the high hardness and superelasticity can help the coating to resist cavitation erosion and the high toughness can delay the expansion of cracks during the cavitation erosion test. As a result, after cavitation erosion for 300 min the cumulative mass loss of the coating sealed by epoxy resin was 1/5 times as much as that of the nitinol coating without sealing. Therefore, the cavitation erosion resistance of the nitinol coating can be improved by sealed with epoxy resin. Abstract : After the coating was sealed with epoxy resin, the pores and cracks of the coating were filled with epoxy resin, the hardness increased, the energy recovery ratio was improved and the toughness was enhanced. As a result, the cavitation erosion resistance of the nitinol coating can be improved by sealing with epoxy resin.